DEGRADASI MORAL DALAM PERSPEKTIF SEMIOTIKA ROLAND BARTHES PADA IKLAN LAYANAN MASYARAKAT “GADGET-SAD STORY” - Andriani, Viena Wanidha (INCARE, International Journal of Educational Resources, 2022)
Public Service Announcement, as one of the communication technique to the society, has certain purposes and important moral messages that are interesting to analyze. Barthes’ semiotic theory applied in this research to find the denotative meaning, connotative meaning, and myth related to the moral degradation of gadget user in “Gadget-Sad Story”. This research is a qualitative descriptive research. The data is taken from Masdulloh Project Youtube Channel by internet access. The data collection is done by observation and documentation. There are some results of this research; (1) the decline of social sensitivity and social interaction, (2) the loss of harmonious relationship in society, (3) the loss of respect to parents, and (4) the loss of self-awareness as the effect of using gadget without a good control.